We Need to Do This A History of the Women's Shelter Movement in Alberta and the Alberta Council of Women's Shelters - Zabjek, Alexandra (LCR Publishing Services, 2023)
In Canada, a woman is killed by her intimate partner every six days. Alberta has one of the highest rates of domestic violence in the country. Starting in the 1970s, Alberta women's shelters have assisted women in crisis. Much more than a safe place to sleep, shelters work to prevent violence through education and training, connect people and communities, and support the complex needs of survivors through a multitude of services. We Need to Do This is the story of Alberta women's shelters. Based on dozens of in-depth interviews, it traces the evolution of a progressive social movement in a traditionally conservative province. These are the stories of women whose voices may otherwise never have been heard: entry-level workers at fledgling shelters battling the assumption that their facilities would create crime, small-town shelter directors forced to self-censor or lose communityand financialsupport, Indigenous women fighting to serve their sisters in Indigenous spaces. Beginning with the women who founded the first shelters, and continuing through the establishment of the Alberta Council of Women's Shelters to the present day, We Need to Do This is a story of hope and survival for the women's shelter movement and for the mothers, sisters, aunts, cousins, and daughters it continues to serve.